Analisa Penghawaan dan Pencahayaan terhadap Kenyamanan Termal pada Rindang Cafe and Eatery Palembang - Wulandari, Riski; Zulfikri, Zulfikri (Universitas Muhammadiyah Palembang, 2024)
Rindang Cafe and Eatery Palembang is one of the cafes that applies the open concept. The use of this concept is expected to reduce artificial energy consumption, including lighting and ventilation, so as to ensure the comfort of a building. This research uses a quantitative approach that evaluates theory by explicitly measuring variables in the field. Opening area, temperature, and humidity were measured using a thermometer, hydrometer, and meter. This research uses a quantitative approach that evaluates theory by measuring variables explicitly in the field. The purpose of this study is to determine the level of thermal comfort in cafes that operate with different air conditioning and lighting conditions from afternoon to evening. This study shows that thermal comfort at Rindang Cafe and Eatery Palembang is strongly influenced by the layout of the air conditioning and lighting. The findings have important implications for the design of cafes and other open space facilities in areas with hot climates.